THEORETICAL QUESTIONS OF INVESTMENT RISK RESEARCH, ITS MAIN FEATURES AND CLASSIFICATION - I. A. Kadyrbaev (Модернизация, инновация, развитие, 2016)
The article examines framework methodology of investment risk. The subject of the study are the basic theoretical positions directly related to the economic category of "investment risk". The purpose of this writing is the improvement of the methodology of the study of investment risk in the investment activity. This objective is to define the tasks, which consist in the formulation of the concept of "investment risk", the development of investment risk classification to provide investors with effective protection against such risks. The implementation  of the tasks will create conditions for the growth of investments in Russia. Currently, effective investment strategy for such an increase, is among the priority directions of development of the Russian economy.The article deals with logically interrelated study of basic economic categories, influencing directly on the investment risk. Author provided classification of investments in accordance with the level of risk. Examine the matter of the financial-economic category of the concept of "investment risk" and the classification of investment risks. Specified main features of the investment risk, which allowed to reveal specifics, which consists in the redistribution of capital in various types of assets in order to maximize profits or to obtain significant social effect.